2014
DOI: 10.1111/ggi.12301
|View full text |Cite
|
Sign up to set email alerts
|

Effectiveness of an oral health educational program on community‐dwelling older people with xerostomia

Abstract: The present study suggests that the educational program targeting oral function improvement is effective among the independent older population.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
66
0
2

Year Published

2017
2017
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 61 publications
(71 citation statements)
references
References 40 publications
(49 reference statements)
3
66
0
2
Order By: Relevance
“…Moreover, stimulations caused during oral care may affect the swallowing reflex and may improve swallowing ability 21. Furthermore, oral massage improves the flow rate of saliva in patients with xerostomia 22,23. Thus, management of oral condition might prove beneficial because of its association with the teeth health and other conditions, such as oral dryness, dysphagia and pneumonia.…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, stimulations caused during oral care may affect the swallowing reflex and may improve swallowing ability 21. Furthermore, oral massage improves the flow rate of saliva in patients with xerostomia 22,23. Thus, management of oral condition might prove beneficial because of its association with the teeth health and other conditions, such as oral dryness, dysphagia and pneumonia.…”
Section: Discussionmentioning
confidence: 99%
“…These items are greatly influenced by the dental (e.g. number of remaining teeth, vertical dimension of occlusion, pairs of functional occlusal contacts, edentulism, presence of removable or fixed prostheses) and periodontal status (pocket depth, inflammation and subgingival calculus) (1,5,6,11,25) . In contrast, mobility was neither different between groups nor significantly associated with both age and OHX in the 82 participants.…”
Section: Discussionmentioning
confidence: 99%
“…Particularly, the tongue was more negatively affected than other components and its weakness associated with aging has been linked to sarcopenia (4,8) . Moreover, mobility tasks encompass combined sensory ability, muscle strength, and precision of movement, which are in general reduced in older adults and can impair orofacial functions, negatively affecting the nutritional status and systemic health (1,(3)(4)(5)(6)(7)(8) .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The intervention group exhibited an improvement in the salivary flow rate, in addition to other functional gains. Recently, Ohara et al 28 performed a similar study using OHEP with 47 elderly patients with xerostomia. The authors demonstrated that educational strategies (oral hygiene instruction, salivary gland massage and muscular exercises for the tongue and face) are effective for the control of xerostomia.…”
Section: Chart 3 -Descriptionmentioning
confidence: 99%